Evaluation of Dietary Acidifiers in Low Acid-Binding Capacity-4 (ABC-4) Diets on Nursery Pig Performance and Fecal Dry Matter - Ethan B. Stas; Mike D. Tokach; Joel M. DeRouchey; Jason C. Woodworth; Robert D. Goodband; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2024)
A total of 300 pigs (DNA 241 × 600, initially 13.2 lb) were used to evaluate dietary acidifiers in low acid-binding capacity-4 (ABC-4) diets on nursery pig performance and fecal dry matter (DM). At weaning, pigs were randomly allotted to one of six dietary treatments. There were five pigs per pen and 10 replications per treatment. Pigs were fed experimental diets in two phases with phase 1 fed from d 0 to 10 post-weaning followed by phase 2 from d 10 to 24. Four diets were formulated to an ABC-4 level of 200 and 250 meq/kg in phases 1 and 2, respectively, by utilizing four different dietary acidifiers. Dietary acidifiers included 0.36% fumaric acid (Primary Products Ingredients Americas LLC, Decatur, IL), 0.87% Activate DA (Novus, St. Charles, MO), 1.01% KEM-GEST (Kemin, Des Moines, IA), and 0.85% ACID-AID (Alltech, Nicholasville, KY). Diet 5 did not include any dietary acidifiers, which increased the ABC-4 level by 40 meq/kg in both phases. All diets contained 110 ppm of Zn provided by the trace mineral premix. Diet 6 was the same formulation as diet 5, but with the addition of 3,000 and 2,000 ppm of Zn from ZnO in phases 1 and 2, respectively. The addition of ZnO further increased the ABC-4 level of the diet by 87 and 54 meq/kg in phases 1 and 2, respectively. Following phase 2 experimental diets, all pigs were fed a common corn-soybean meal-based diet until the completion of the study on d 38 post-weaning. There were no differences (P > 0.05) observed between pigs fed the four dietary acidifiers for the duration of the study. In phase 2 (d 10 to 24), the experimental period (d 0 to 24), and overall (d 0 to 38), pigs fed the low ABC-4 diets containing acidifiers had improved (P ≤ 0.020) F/G compared to pigs fed the higher ABC-4 diet (without acidifiers). In the experimental period (d 0 to 24), pigs fed diets containing ZnO tended to have improved (P = 0.052) F/G compared to pigs fed diets without added ZnO. In conclusion, utilizing dietary acidifiers to achieve a low ABC-4 level improved feed efficiency. The specific dietary acidifier utilized to target a low ABC-4 level did not affect the growth response in nursery pigs. However, most dietary acidifiers were included above their supplier-recommended inclusion rates to achieve the targeted low ABC-4 level and removing them only increased the ABC-4 by 40 meq/kg. Therefore, other aspects of diet formulation such as low ABC-4 specialty protein or lactose sources, low Ca levels, a combination of acidifiers, or other methods must be considered when targeting low ABC-4 levels.
Keywords: acid-binding capacity; acidifiers; nursery pigs